Release of Gentamicin and Vancomycin from Preformed Spacers in Infected Total Hip Arthroplasties: Measurement of Concentrations and Inhibitory Activity in Patients’ Drainage Fluids and Serum - Dario Regis; Andrea Sandri; Elena Samaila; Anna Benini; Manuel Bondi; Bruno Magnan (The Scientific World Journal)
Gentamicin (G) and vancomycin (V) concentrations in drainage fluids obtained from patients during the first 24 hours after implantation of antibiotic-loaded polymethylmethacrylate (PMMA) spacers in two-stage revision of infected total hip arthroplasty were studied. The inhibitory activity of drainage fluids against different multiresistant clinical isolates was investigated as well. Seven hips were treated by implantation of industrial G-loaded spacers. Vancomycin was added by manually mixing with PMMA bone cement. Serum and drainage fluid samples were collected 1, 4, and 24 hours after spacer implantation. Antibiotics concentrations and drains bactericidal titer of combination were determined against multiresistant staphylococcal strains. The release of G and V from PMMA cement at the site of infection was prompt and effective. Serum levels were below the limit of detection. The local release kinetics of G and V from PMMA cement was similar, exerting a pronounced, combined inhibitory effect in the implant site. The inhibitory activity of drainage fluids showed substantial intersubject variability related to antibiotic concentrations and differed according to the pathogens tested. Gentamicin and vancomycin were released from temporary hip spacers at bactericidal concentrations, and their use in combination exerted strong inhibition against methicillin-resistant S. aureus and Coagulase Negative Staphylococci strains.